Optimizing production conditions, sensory attributes, and consumer acceptance of gaba soy sauce using Aspergillus sp., Bacillus sp., and Tetragenococcus sp. and sustainable production strategies / Chong Shin Yee - Chong , Shin Yee (2024)
The rising demand for functional foods has sparked an interest in boosting the nutritional value of conventional condiments such as soy sauce. Recent soy sauce research has focused on enhancing functional gamma-aminobutyric acid (GABA) by microorganisms since the key inhibitory neurotransmitter provides various health benefits, including anti-anxiety and anti-stress effects. However, optimizing fermentation conditions to increase GABA production with microorganisms remains challenging, specifically, difficulty in balancing multiple fermentation variables such as pH, inoculum percentage, and agitation speed, which interact to impact GABA production levels. These complexities make it hard to achieve optimal conditions for producing a high-quality GABA soy sauce. Additionally, the existing scholarly literature on the sustainability of soy sauce production is relatively scattered. The primary goals of the present study were to determine the ideal fermentation conditions to maximize GABA concentration in soy sauce production using Response Surface Methodology (RSM), assess consumers’ acceptance of GABA soy sauce through sensory analysis, and design a sustainable soy sauce production via a systematic review. The fermentation conditions, including the percentage of bacterial inoculum (10, 15, and 20%), initial pH (3, 5, and 7), and agitation speed (100, 150, and 200 rpm), were optimized using RSM with a mixed culture containing Aspergillus oryzae strain NSK, Bacillus cereus strain KBC and Tetragenococcus halophilus strain KBC. The mixed cultures generated 128.69 g/L of GABA after 7 days of fermentation. Remarkably, 239.08 g/L of GABA was produced after 4 weeks of fermentation with 20% of inoculum, initial pH 7, and 100 rpm, which was iv 36% higher than non-optimized conditions (153.48 g/L). Meanwhile, the sensory analysis revealed that fermented GABA soy sauce received higher consumer acceptance (7.46) than the control (5.90) and commercial soy sauces (4.47). Consumer preference indicated that the starter culture offered a better umami taste while reducing the presence of bitter, sour, and salty tastes compared to the commercial products. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) analysis was performed to facilitate sustainable soy sauce production, applying inclusion criteria to the Scopus and Web of Science databases. The systematic review identified existing gaps in soy sauce fermentation research and proposed future research possibilities, with a particular emphasis on sustainable soy sauce technologies and techniques that could contribute to advancements in soy sauce production. This study proves that under optimal fermentation conditions determined by RSM statistical analysis, the mixed culture demonstrates a remarkable ability to generate high levels of GABA and greatly enhances consumer acceptability toward this GABA-enriched soy sauce. This study provides valuable insights for industry stakeholders interested in sustainable food production, highlighting the potential for health benefits and increased market viability.